GTAW WELDING DEFECTS ANALYSIS WITH WELDING CURRENT LEVEL AND TUNGSTEN DIAMETER PARAMETERS ON ST-37 STEEL - Nafi, Maula; Wahid, Ichlas; Wantara, Ronny Wahyu; Primaningtyas, Widya Emilia; Marsuki, Ismail (International Conference of Innovation and Community Engagement, 2024)
Gas Tungsten Arc Welding (GTAW) is a widely used welding method in the construction industry due to its high precision and efficiency. This study objective is to identify welding defects in ST-37 steel using parameters in tungsten electrode diameters and welding current. The tungsten electrode diameters used were 1.6 mm, 2.4 mm, and 3.2 mm, with current levels of 60 A, 80 A, and 100 A. After welding, a penetrant test was conducted according to ASME 2010 Section 6 standards to identify the types and number of welding defects. The test results indicated that the combination of a 3.2 mm tungsten electrode and a 60 A current produced the highest number of defects, with eight instances of porosity, cracks, and tungsten inclusions. In contrast, the same 3.2 mm electrode with a 100 A current resulted in the fewest defects, with only two defects identified, namely cluster porosity and tungsten inclusion. These findings suggest that higher current levels in GTAW welding tend to reduce the occurrence of welding defects in ST-37 steel, whereas lower current levels increase the likelihood of defects. This information is crucial for optimizing welding parameters in industrial applications. Keywords: Current Level, Defects, Electrode, Gas Tungsten Arc Welding, ST-37 Steel